Metformin Alters Human Host Responses to Mycobacterium tuberculosis in Healthy Subjects - Lachmandas, Ekta; Eckold, Clare; Böhme, Julia; Koeken, Valerie A C M; Marzuki, Mardiana Binte; Blok, Bastiaan; Arts, Rob J W; Chen, Jinmiao; Teng, Karen W W; Ratter, Jacqueline; Smolders, Elise J; Van den Heuvel, Corina; et al. (The Journal of infectious diseases, 2019)
Abstract Background Metformin, the most widely administered diabetes drug, has been proposed as a candidate adjunctive host-directed therapy for tuberculosis, but little is known about its effects on human host responses to Mycobacterium tuberculosis. Methods We investigated in vitro and in vivo effects of metformin in humans. Results Metformin added to peripheral blood mononuclear cells from healthy volunteers enhanced in vitro cellular metabolism while inhibiting the mammalian target of rapamycin targets p70S6K and 4EBP1, with decreased cytokine production and cellular proliferation and increased phagocytosis activity. Metformin administered to healthy human volunteers led to significant downregulation of genes involved in oxidative phosphorylation, mammalian target of rapamycin signaling, and type I interferon response pathways, particularly following stimulation with M. tuberculosis, and upregulation of genes involved in phagocytosis and reactive oxygen species production was increased. These in vivo effects were accompanied by a metformin-induced shift in myeloid cells from classical to nonclassical monocytes. At a functional level, metformin lowered ex vivo production of tumor necrosis factor α, interferon γ, and interleukin 1β but increased phagocytosis activity and reactive oxygen species production. Conclusion Metformin has a range of potentially beneficial effects on cellular metabolism, immune function, and gene transcription involved in innate host responses to M. tuberculosis. Metformin has shown beneficial effects in a murine model of tuberculosis. Using in-vitro and in-vivo studies we show that metformin has beneficial effects on cellular metabolism, immune function and genetranscription involved in innate host responses to M. tuberculosis in humans.